(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2013)
The return of realism that followed the Postmodern years, marks an ontological “turn” which is not free of consequences also in relation to theories on cinema. This essay aims at analysing the existing relationship between the aesthetic-perceptive experience – through the notion of “immediate experience” – and the notion of “reality” in the cinematographic image. The link image-reality is considered here as a “phenomenon” in itself. If the phenomenal experience could be intended as such, without a subject, the cinematographic image too could be intended as a look without subjectivity. Cinema takes us beyond phenomenology, or rather, inside a “heretic” phenomenological perspective.